2019
DOI: 10.1111/cpr.12614
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA DOCK1 promotes bladder carcinoma progression via modulating circDOCK1/hsa‐miR‐132‐3p/Sox5 signalling pathway

Abstract: Objectives To reveal the role of circular RNA (circRNA) DOCK1 (circDOCK1) as a potential biomarker and therapeutic target and its competing endogenous RNA mechanism in bladder carcinoma (BC). Methods The next‐generation sequencing (NGS) technology was introduced to screen the circRNA expression profiles of BC using microarray. qPCR and Western blots assay were employed to measure the gene expression in different groups. Cell counting kit‐8, EdU and transwell assays were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 41 publications
(68 reference statements)
2
58
0
Order By: Relevance
“…Recent evidences have suggested that circRNAs involve in far‐ranging biological processes, including transcription, mRNA splicing, RNA decay and translation, and their deregulation takes pivotal roles in the development and metastasis of various tumors, such as glioma, 15 hepatoblastoma, 16 colorectal cancer, 17 lung cancer, 18 prostate cancer, 19 bladder cancer, 20 and gastric cancer 21 . For example, Li et al revealed that circANKS1B promotes colorectal cancer cell migration and invasion by working as a molecular sponge of miR‐149 to regulate FOXM1 and Slug protein expressions 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidences have suggested that circRNAs involve in far‐ranging biological processes, including transcription, mRNA splicing, RNA decay and translation, and their deregulation takes pivotal roles in the development and metastasis of various tumors, such as glioma, 15 hepatoblastoma, 16 colorectal cancer, 17 lung cancer, 18 prostate cancer, 19 bladder cancer, 20 and gastric cancer 21 . For example, Li et al revealed that circANKS1B promotes colorectal cancer cell migration and invasion by working as a molecular sponge of miR‐149 to regulate FOXM1 and Slug protein expressions 17 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been showed that hsa_circ_0007059 abates cell proliferation and EMT progress in lung cancer cells through inactivation of Wnt/β‐catenin and ERK1/2 pathways via inhibiting miR‐378 18 . In BC, Liu et al demonstrated that circDOCK1 promotes BC progression through modulation of circDOCK1/hsa‐miR‐132‐3p/Sox5 pathway in vitro and in vivo as well as acts as a promising biomarker and therapeutic targets for BC 20 . And notably, our preliminary works have illustrated that high expression of circASXL1 in BC connects with poor TNM classification and may independently predict overall survival (OS) for patients with BC 22 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that circular RNAs (circRNAs) are involved in tumour progress. 3,4 Through their regulatory functions, circRNAs could act as oncogenes or tumour suppressors in tumour progression, which indicates that circRNAs could be novel biomarkers or targets for tumour treatment. 5,6 However, the expression and function of circRNAs in glioma are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-132-3p was a tumor suppressor miRNA in multiple cancers, including mesothelioma, bladder carcinoma and breast cancer [21][22][23]. Previous studies have covered the low level of miR-132-3p in CRC compared with normal samples, and overexpression of miR-132-3p restrained the proliferation and metastasis of CRC cells [24].…”
Section: Discussionmentioning
confidence: 99%